2003
DOI: 10.3354/dao057109
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of adhesion properties of Ruditapes philippinarum hemocytes exposed to Vibrio tapetis

Abstract: Vibrio tapetis is the causative agent of brown ring disease (BRD), which affects a species of clam, Ruditapes philippinarum. After incubation with V. tapetis, hemocytes lose filopods and become rounded, indicating cytotoxic activity of the bacterium. To rapidly quantify this cytotoxicity, a flow-cytometry test was developed based on the capacity of V. tapetis to inhibit adhesion of clam hemocytes to plastic. Several bacteria:hemocyte ratios, the cytotoxicity of other Vibrio spp. pathogenic to bivalves, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 42 publications
7
84
0
1
Order By: Relevance
“…Indeed, standardized in vitro assays are necessary to screen for distinct activities covered by the generic term virulence, such as adherence and cytolytic effects. However, marine invertebrate cell lines do not exist, and so far the experiments to examine interactions between cells and pathogenic vibrios rely on primary lines of hemocytes maintained under survival conditions (4,8,23). Nevertheless, the use of such a cell population has drawbacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, standardized in vitro assays are necessary to screen for distinct activities covered by the generic term virulence, such as adherence and cytolytic effects. However, marine invertebrate cell lines do not exist, and so far the experiments to examine interactions between cells and pathogenic vibrios rely on primary lines of hemocytes maintained under survival conditions (4,8,23). Nevertheless, the use of such a cell population has drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation was carried out with 3.7% paraformaldehyde in PHEM buffer (for 1 liter, add 18.14 g of PIPES, 6.5 g of HEPES, 3.8 g of EGTA, and 0.99 g of MgSO 4 and adjust the pH to 7.0 with 10 M KOH). The observation of the formazan needle-like crystals present at the cell surface after MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] treatment was performed by diffraction interference contrast (DIC) microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, however, the P-selectins are known to be involved in adhesion processes (Rudenko et al, 1999;Grishkovskaya et al, 2000;Tisi et al, 2000;Buschiazzo et al, 2002), and studies have shown that some virulence factors present in the excretion-secretion products of marine Vibrio spp. reduced the adhesive properties of invertebrate hemocytes (Choquet et al, 2003;Allam and Ford, 2006;Labreuche et al, 2006a;Labreuche et al, 2006b;Mateo et al, 2009). Hemocytelike cells have not yet been identified in scleractinians, but endodermal and circulating granular and agranular cells may have phagocytic properties (Mullen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(d) Adhesion of the hemocytes was measured by assessing the proportion of hemocytes that detach from the surface of experimental chambers after incubation with potential toxins as previously described for clams by Choquet et al (2003). The assay was conducted in 24-well plates.…”
Section: Analysis Of Hemocyte Parametersmentioning
confidence: 99%